Traduire le devoir être. Stanisław Barańczak, Et aujourd’hui?, poème - Nowotna, Magdalena (Romanica Silesiana)
Magdalena Nowotna analyses the system of the said, directly and allusively, as well the unsaid in the poem by Barańczak, in the perspective of the translation into French. Keywords: literary translation; Polish poetry; Barańczak; what-should-be-there